The Impacts of Flood and Drought on Food Security in Central Java - Endita Prima Ari Pratiwi; Eka Laily Ramadhani; Fatchan Nurrochmad; Djoko Legono (Journal of the Civil Engineering Forum, 2020)
To achieve food security, water must be available at the right place, at the right time, in the right quantity, and be of the right quality. Water-related disasters will negatively affect agricultural areas and crop production, which can threaten food security. Nevertheless, flood and drought strike Central Java, one of the rice production centres in Indonesia, every year, and climate change has been worsening the condition because extreme events occur more frequently. This study reviews the impacts of flood and drought on paddy fields in Central Java from 2014 to 2018. A set of historical documents, including reports on flood and drought, rainfall records, and rice production, were collected from government institutions. Quantitative analysis was conducted using statistics and geographic information system tools. The results showed that the 2014 flood event reflected badly on 94,306 hectares (ha) paddy fields. Four severely affected regencies were Pati (25,460 ha), Demak (13,560 ha), Jepara (13,281 ha), and Kudus (12,203 ha). Meanwhile, drought in 2015 affected 82,324 ha paddy field. The areas severely damaged by drought were Blora (12,335 ha), Cilacap (11,503 ha), Grobogan (10,514 ha), and Pemalang (10,134 ha). Pearson’s correlation analysis results indicated that the correlation between annual rainfall and drought impact (r = −0.865, p = 0.058) is more significant than that between annual rainfall and drought impact (r = 0.794, p = 0.108). The stakeholders have adopted some strategies to minimise losses, such as establishing a 1,000 small water reservoirs program, preparing temporary pump irrigation, and providing agricultural insurance. Nevertheless, more efforts are still necessary to fight against food insecurity.